The Outsider’s Gaze: Reflections on recent non-Byzantinist Readings of Byzantine History and on their Implications for our Field - KRALLIS, Dimitris (Byzantina Symmeikta, 2014)
The present essay reviews recent work on Byzantium, its politics, religion, and culture published outside the world of Byzantine Studies and discusses the significance of such readings for the evolving relationship of our field with audiences both lay and academic.